If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -60 = 3 + -7x Solving -60 = 3 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -60 + 7x = 3 + -7x + 7x Combine like terms: -7x + 7x = 0 -60 + 7x = 3 + 0 -60 + 7x = 3 Add '60' to each side of the equation. -60 + 60 + 7x = 3 + 60 Combine like terms: -60 + 60 = 0 0 + 7x = 3 + 60 7x = 3 + 60 Combine like terms: 3 + 60 = 63 7x = 63 Divide each side by '7'. x = 9 Simplifying x = 9
| 49=3x+2(x+2) | | 2/9n=2/3 | | (X-6)(x-4)=0 | | 3x+2(x+2)=49 | | 13(x-2)-2x=4-5(x+3) | | p=2x+2wforx | | 2x^4-10x^3-3x^2=0 | | 4(3x+2)=50 | | (4x-5)(6x+5)=0 | | 5(x-3)-1=-41 | | 7x+3(x-2)=44 | | -21x=3 | | 2x-9=x/2 | | 3x+2x=8x-3 | | (1/x+3)-(1/x+4)=1/2 | | 3/5y-3y=-4 | | -7+8x+10+(-11x)= | | 10h=90 | | 3x+4x=136 | | 5(x-3)+4x=-60 | | -6+1/4w=-4 | | 4-21x=7 | | 20=4w+2(w-5) | | -6p-3=-8-5p | | 4x+3(x+2)=41 | | 8p+4=10+7p | | 7(x+2)+8x=-1 | | 21=15-6n | | 5y+(-3x)-7x+1-3y+2= | | 13+5=313 | | 18x^2+11x=0 | | 2x+14=6x+34 |